2016
DOI: 10.1111/hdi.12443
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of blood flow rate on dialysis with self‐centering CentrosFLO catheter: A multicenter prospective study

Abstract: Introduction Chronic central venous catheters (CVC) for dialysis lose patency and deliver lower blood flow over time, often due to fibrous sheathing that covers the lumen tips. The CentrosFLO central venous catheter has a shape that directs the arterial and venous tips away from the walls of the vena cava and right atrium, making sheathing of the tips less likely. Methods A prospective, multicenter, single arm, non-controlled, observational study was conducted at eight sites in the United States. All consentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The self-centering catheter is designed to prolong CVC survival by preventing the end holes from coming into direct contact with the vessel wall, which can lead to fibrin sheath formation and encasement of the end holes and vascular injury. Several prospective clinical trials have indicated a high patency of the self-centering catheter, with approximately 90% patency after 3 months of use (20,31,32). This patency compares favorably to numerous studies of other catheters (32).…”
Section: Lumen and Tip Design Of Long-term Cvcsmentioning
confidence: 66%
See 1 more Smart Citation
“…The self-centering catheter is designed to prolong CVC survival by preventing the end holes from coming into direct contact with the vessel wall, which can lead to fibrin sheath formation and encasement of the end holes and vascular injury. Several prospective clinical trials have indicated a high patency of the self-centering catheter, with approximately 90% patency after 3 months of use (20,31,32). This patency compares favorably to numerous studies of other catheters (32).…”
Section: Lumen and Tip Design Of Long-term Cvcsmentioning
confidence: 66%
“…Several prospective clinical trials have indicated a high patency of the self-centering catheter, with approximately 90% patency after 3 months of use (20,31,32). This patency compares favorably to numerous studies of other catheters (32). Although one of these trials was multicenter, none were prospectively controlled.…”
Section: Lumen and Tip Design Of Long-term Cvcsmentioning
confidence: 88%
“…39 In a continuous effort to improve catheter patency rate and reduce complications, the self-centering CentrosFLO catheter was developed. 40 This catheter is an iteration of the split-tip prototype in which both the arterial and venous limbs of the catheter are curved, forming an oval shaped configuration. The side ports are directed inward to prevent contact with the vessel wall, a merit that hinders fibrin sheath formation and encasement of the side ports (►Fig.…”
Section: Hemodialysis Catheter Lumen and Tip Designmentioning
confidence: 99%
“…A casualty of this dispute with Medcomp was the relationship we had developed between our two companies. Some years later I designed a split‐tip catheter with two tips bending inward (CentrosFLO™) to avoid fibrous sheathing of the tips 9 . This catheter was licensed to another company, not Medcomp.…”
Section: Figurementioning
confidence: 99%
“…Some years later I designed a split-tip catheter with two tips bending inward (CentrosFLO™) to avoid fibrous sheathing of the tips. 9 This catheter was licensed to another company, not Medcomp.…”
mentioning
confidence: 99%